2020
DOI: 10.5709/acp-0297-5
|View full text |Cite
|
Sign up to set email alerts
|

Vigilance, Inhibitory Control and Regional Cerebral Blood Oxygenation in the PFC - Differences in ADHD Types of Presentations

Abstract: It is commonly believed that proven abnormalities in the structure and functioning of the prefrontal lobes affect cognitive deficits in children with ADHD. The purpose of the current study was to assess vigilance, inhibitory control, and regional cerebral blood oxygenation (rCBO2) in the prefrontal cortex (PFC) of children with ADHD. The study included 150 children with ADHD and 51 typically developing (TD) children aged 9-12 years. Children with ADHD showed a deficit in vigilance (assessed by the shortened ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Decreased frontal lobe perfusion is a consistent finding in ADHD across multiple SPECT studies ( 327 , 338 345 ) and confirmed by multiple functional MRI studies ( 346 , 347 ) and infrared spectroscopy ( 348 ). For example, SPECT scans of medication-naïve children with ADHD ( N = 40) were compared to normal controls using statistical parametric analysis ( 338 ).…”
Section: Assessment Of the State Of The Art—spect In Brain Disordersmentioning
confidence: 61%
“…Decreased frontal lobe perfusion is a consistent finding in ADHD across multiple SPECT studies ( 327 , 338 345 ) and confirmed by multiple functional MRI studies ( 346 , 347 ) and infrared spectroscopy ( 348 ). For example, SPECT scans of medication-naïve children with ADHD ( N = 40) were compared to normal controls using statistical parametric analysis ( 338 ).…”
Section: Assessment Of the State Of The Art—spect In Brain Disordersmentioning
confidence: 61%
“…Specifically, sleep deprivation attenuates activation of various parietal and frontal cortical regions, including the prefrontal cortex 44 , 45 , which plays a central role in sustained attention. Notably, ADHD is associated with lower activation in the prefrontal cortex during tasks that involve attention 46 and inhibitory control tasks 47 . Thus, sleep deprivation may aggravate the deficits in the functioning of the prefrontal cortex and related regions, leading to a more severe disruption in the performance of tasks that require sustained attention.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, these neuroimaging findings have been replicated using a newer technique of infrared spectroscopy ( 72 ). A sample of 150 children with ADHD were compared to 51 controls in a series of concentration tasks.…”
Section: Discussionmentioning
confidence: 99%